Peran Tokoh Adat Batak Toba dalam Membentuk Perilaku Memilih pada Pemilihan Kepala Desa Ujung Serdang Tahun 2022 - Yeremia Elkana Tua Siburian; Halking Halking (Majalah Ilmiah METHODA, 2025)
This study aims to analyze the role of Batak Toba traditional leaders in shaping voting behavior during the 2022 village head election in Ujung Serdang Village, as well as to reveal their significant role in influencing the political behavior of local residents. The research was conducted in Ujung Serdang Village, a community with a strong Batak Toba population that upholds traditional cultural values, despite being situated in a modern urban area. The subjects of the study include influential traditional leaders and residents of Ujung Serdang Village. The research employed a qualitative descriptive method, with data collection techniques comprising structured interviews, literature review, and documentation. Data analysis was carried out through stages of data collection, reduction, presentation, and conclusion drawing. The findings indicate that traditional leaders play a crucial role as agents of political socialization in influencing voting behavior during the Ujung Serdang village head election. Their roles include mobilizing, guiding, supervising, and engaging in decision-making. This influence is rooted in local cultural values such as Dalihan Na Tolu, which serves as a moral and social compass in leadership selection. However, the dynamics of voting behavior in Ujung Serdang show a shift, where rational considerations based on the candidates' visions, missions, and programs are becoming more dominant, surpassing purely social or emotional ties. This dominance of a rational approach reflects a growing political awareness and a desire among the community to elect leaders who offer real change and tangible progress. Although traditional leaders remain significant as mediators, agents of political socialization, and guardians of customary norms, their influence increasingly depends on the ability of the candidates they support to persuade voters with measurable ideas and plans. The interaction between traditional authority and voter rationality ultimately shapes the election outcome, reflecting an evolution in the democratic process at the local level.